PERBANDINGAN EFEKTIVITAS PERUBAHAN WARNA GIGI SETELAH APLIKASI PIR HIJAU (PYRUS COMMUNIS) DENGAN KARBAMIDA PEROKSIDA 16% SEBAGAI BAHAN HOME BLEACHING - Viona Diansari; Iin Sundari; Reza Aulia (Journal of Syiah Kuala Dentistry Society, 2019)
The home bleaching procedure is a tooth whitening process that can be done at home using a prostheticlikedevicecalledatrayornightguardwith16%carbamideperoxideconcentration.Chemicalssuchascarbamideperoxidecanhaveasensitiveeffectontheteeth.Greenpear(Pyruscommunis)isbelievedtohaveacontentthatcanremovestainsonthesurfaceoftheteethandwhitenteethsuchasmalicacid,citricacid, oksalat acid, sicamat acid, fumarate acid, tartaric acid and lactic acid. This study was alaboratory experimental study of the effectiveness of tooth discoloration applied with green pears(Pyrus communis) and then compared with the color of teeth applied to 16% carbamide peroxide. Toothcolor changes that occurs is measured using the shade guide. In the group of green pear juice (Pyruscommunis) it produces the final color A3.5 and A3, while in the carbamide peroxide group 16%produces the final color A1. The results of the study were analyzed using Wilcoxon and Mann Whitneyanalysis to see the comparison of the effectiveness of tooth color change in the teeth. Based on theresults of the study it can be concluded that the application of green pear (Pyrus communis) is lesseffective than the application of 16% carbamide peroxide.Keywords: Green Pear (Pyrus communis), Carbamide Peroxide, Home Bleaching